Effect of Layer Deposition and Thermal Treatment on the Structural, Optical, and Electrical Characteristics of Spin-Coated CaTiO3 Thin Films - Yusron, Darojat; Mustafida, Aulia; Abdul, Rajak; Indra, Pardede (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
This study investigates the effect of coating repetition and annealing temperature on the structural, optical, and electrical characteristics of calcium titanate (CaTiO3) thin films synthesized via a sol-gel spin coating method. The number of coatings (2, 4, 6, and 8 layers) and annealing temperatures (250 C, 350 C, and 450 C) were varied to optimize the characteristics. X-ray diffraction analysis indicated an improvement in crystallinity with increasing annealing temperature, as evident from the growing diffraction peaks. UV-Vis spectroscopy revealed a decrease in the optical band gap from 3.741 eV to 3.554 eV with increasing coating layers and thermal treatment, suggesting enhanced optical absorption. Current-voltage measurements using a two-point probe method generally showed linear conduction, indicative of ohmic behavior, with one sample exhibiting a mild nonlinear response at higher bias. The results confirm that process parameters significantly influence the functional properties of CaTiO3 thin films. This fundamental study provides a foundation for employing CaTiO3 as a functional layer in perovskite-based photovoltaic devices, paving the way for further device integration and optimization.